Descriptive epidemiology of measles cases in Bauchi State, 2013-2018 - Polycarp Uchechukwu Ori; Ayo Adebowale; Chukwuma David Umeokonkwo; Ugochukwu Osigwe; Muhammad Shakir Balogun (BMC, 2021)
Abstract Background Measles accounts for high morbidity and mortality in children, especially in developing countries. In 2017, about 11,190 measles cases were recorded in Nigeria, including Bauchi State. The aim of this study was to describe the trend and burden of measles in Bauchi State, Nigeria. Method We analyzed secondary data of measles cases extracted from the Measles Surveillance data system in Bauchi State from January 2013 to June 2018. The variables extracted included age, sex, doses of vaccination, case location and outcome. Data were analyzed using descriptive statistics, logistic regression, and multiplicative time series model (α = 0.05). Results A total of 4935 suspected measles cases with an average annual incidence rate of 15.3 per 100,000 population and 57 deaths (Case Fatality Rate, CFR: 1.15%) were reported. Among the reported cases, 294 (6%;) were laboratory-confirmed, while clinically compatible and epi-linked cases were 402 (8%) and 3879 (70%), respectively. Of the 4935 measles cases, 2576 (52%) were males, 440 (9%) were under 1 year of age, and 3289 (67%) were between 1 and 4 years. The average annual incidence rate among the 1-4 year age-group was 70.3 per 100,000 population. The incidence rate was lowest in 2018 with 2.1 per 100,000 and highest in 2015 with 26.2 per 100,000 population. The measles cases variation index per quarter was highest in quarter 1 (198.86), followed by quarter 2 (62.21) and least in quarter 4 (10.37) of every year. Only 889 (18%) of the measles cases received at least one dose of measles vaccine, 2701 (54.7%) had no history of measles vaccination while 1346 (27.3%) had unknown vaccination status. The fatality of measles in Bauchi State were significantly associated with being under 5 years (AOR = 5.58; 95%CI: 2.19-14.22) and not having at least a dose of MCV (OR = 7.14; 95%CI: 3.70-14.29). Conclusion Measles burden remains high in Bauchi State despite a decrease in its incidence over the study years. Most of the cases occurred in the first quarter of every year. Improved routine measles surveillance for prompt case management could reduce the burden of the disease in Bauchi State.